Search of Allosteric Inhibitors and Associated Proteins of an AKT-like Kinase from Trypanosoma cruzi (2018)
ABSTRACT: Proteins associated to the PI3K/AKT/mTOR signaling pathway are widely used targets for cancer treatment, and in recent years they have also been evaluated as putative targets in trypanosomatids parasites, such as Trypanosoma cruzi. Here, we performed a virtual screening approach to find candidates that can bind regions on or near the Pleckstrin homology domain of an AKT-like protein in T. cruzi. The compounds were also evaluated in vitro. The in silico and experimental results allowed us to identify a set of compounds that can potentially alter the intracellular signaling pathway through the AKT-like kinase of the parasite; among them, a derivative of the pyrazolopyridine nucleus with an IC50 of 14.25 ± 1.00 µM against amastigotes of T. cruzi. In addition, we built a protein–protein interaction network of T. cruzi to understand the role of the AKT-like protein in the parasite, and look for additional proteins that can be postulated as possible novel molecular targets for the rational design of compounds against T. cruzi.